Comparative Analysis of Broiler Production Efficiency and Cost of Production in Different Housing Systems - Timbul Sihombing; Novie Andri Setianto; Ismoyowati Ismoyowati; Elly Tugiyanti; Yusmi Nur Wakhidati; Jin Dingxing (Animal Husbandry Department, The Faculty of Agriculture, Universitas Syiah Kuala, 2026)
The broiler industry faces rising input costs and increasing demands for production efficiency, making housing system selection a key factor in technical and economic performance. This study analyzed differences in production performance and cost of production (COP) under open house, semi-closed house, and closed house systems in commercial contract farming in a humid tropical region. Secondary data from 33 broiler production cycles in West Java were analyzed using ANOVA, Games–Howell post hoc test, and Spearman’s correlation. Housing system significantly affected FCR, performance index (PI), and COP, but not slaughter age. The closed house system produced the highest PI, while the lowest COP was observed in the semi-closed house system. FCR showed a very strong positive correlation with COP, whereas ADG and PI were significantly negatively correlated. Feed efficiency is the main determinant of COP, and the semi-closed house system provides an optimal balance between biological efficiency and economic performance.